Document: Hervibors hosts influence on insecticide resistance: a review - Domínguez Gil, O.; McPheron, B. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2012)
Resistance is a worldwide problem, which if ignored or improperly managed, will significantly reduce worldwide agricultural production and public health. Resistance is influenced by genetic factors but also there is an environmental effect, which in the case of phytofagas diseases is partially represented by the chemicals found in the host plants. Species with an evolutionary history of feeding on heavily chemically defended plant structures should have elevated levels of enzymes that detoxify defensive chemicals, and therefore an enhanced ability to evolve resistance to synthetic toxins. The role of host plant chemistry on the expression and evolution of pesticide resistance is reviewed from the perspective of understanding the non-genetic factors influencing pesticide resistance. This perspective is important since environmental factors may have relatively important effects influencing the activity of detoxification enzymes in animals, and hence, susceptibility to xenobiotics. Research on non-genetic factors influencing pesticide resistance must be undertaken if we are to increase our confidence in proposed management strategies.